Peran dan Kontribusi Production Designer dalam Industri Perfilman: Studi Kasus pada Proses Perancangan Produksi Visual - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2023)
In film the role of Production Designer is very important because it is responsible for mise-en-scene writing, which includes the design and visuals of the entire film production. Production Designers have the task of designing and creating design drawings for various elements in the film, such as locations, graphics, props, lighting, scenes, makeup, and costumes. This research will investigate the role and contribution of Production Designers in the film industry, especially in the context of visual production design, revealing a number of challenges and critical aspects that may be faced by Production Designers. What are the new technologies used by Production Designers in the visual production design process? How do production designers balance their creative vision with the constraints and realities of production? What awards have Production Designers received for their contributions to the film industry? The research method used to investigate the role and contribution of Production Designers in the film industry, especially in the context of visual production design is qualitative research methods. The role of a Production Designer in filmmaking is very important, because a Production Designer will be responsible for building the mood and look in the artistic order that will be built on the film according to the concept of the film's story including the use of color. In this research, it has been revealed that Production Designers use various technologies and innovations to produce impressive production designs. By continuing to use innovative technology and creativity, Production Designers will continue to be a major force in creating impressive visuals and changing the way we experience and appreciate film.